Food waste between environmental education, peers, and family influence. Insights from primary school students in Northern Italy. (10th January 2023) - Piras, Simone; Righi, Simone; Banchelli, Federico; Giordano, Claudia; Setti, Marco
Abstract: Education plays a central role in tackling consumers' food waste. However, research on children's food waste at school tends to focus on quantification and logistical factors rather than on the impact of interventions. Furthermore, behavioural elements, including imitation, tend to be neglected despite their well-established role in the food realm. To contribute to filling this gap, we assess the short and long-term impact on food waste levels of a lesson about the environmental consequences of food waste. Innovating on the literature, we control for both behavioural factors and social influence. For this purpose, we developed a longitudinal protocol that factors in altruistic concerns elicited through economic experiments, and the influence of parents and classmates assessed through parents' questionnaires and network questions. We apply the protocol to a sample of 420 Italian primary school students from 20 classes. The lesson was implemented in half of the classes, randomly selected. We find that the lesson only reduces self-declared food waste in the short-term but the impact does not persist after some months. Concerns for the environmental implications of food waste increase significantly, and this effect is still present in the longer-term. Neither the parents' approach to wasting food nor the degree of students' pro-social motivations make a significant difference. In turn, students' food waste is found to align with that of the students sitting nearby in the school canteen, suggesting that imitation through direct observation of behaviours plays an important role. These results call policymakers to take advantage of network effects in social settings to favour the replication of pro-environmental behaviours. Highlights: The impact on children's food waste behaviour of an educational initiative was assessed. A three-wave longitudinal protocol including behavioural experiments and parent surveys was used. The lesson only reduces food waste in the short-term, while awareness of environmental consequences persists. Children's pro-social attitudes and parents' approaches to wasting food make no significant difference. Children's food waste in school canteens is related to the food waste of the children sitting nearby.